Cryo‐EM Resolves Molecular Recognition Of An Optojasp Photoswitch Bound To Actin Filaments In Both Switch States. (4th March 2021) - Pospich, Sabrina; Küllmer, Florian; Nasufović, Veselin; Funk, Johanna; Belyy, Alexander; Bieling, Peter; Arndt, Hans‐Dieter; Raunser, Stefan
Abstract: Actin is essential for key processes in all eukaryotic cells. Cellpermeable optojasps provide spatiotemporal control of the actin cytoskeleton, confining toxicity and potentially rendering F‐actin druggable by photopharmacology. Here, we report cryo electron microscopy (cryo‐EM) structures of both isomeric states of one optojasp bound to actin filaments. The high‐resolution structures reveal for the first time the pronounced effects of photoswitching a functionalized azobenzene. By characterizing the optojasp binding site and identifying conformational changes within F‐actin that depend on the optojasp isomeric state, we refine determinants for the design of functional F‐actin photoswitches. Abstract : Targeting actin requires spatiotemporal control of drug activity. Optojasps are photo‐switchable small molecules, providing direct optical spatiotemporal control of the actin cytoskeleton. We present high‐resolution cryo‐EM structures of both isomeric states of an optojasp bound to F‐actin and describe in detail the binding pocket and conformational changes associated with switching of the azobenzene.